DISTRIBUSI DAN IDENTIFIKASI POPULASI SINTRONG (Crossocephalum crepidiodes.Benth) RESISTEN PARAKUAT PADA LAHAN JAGUNG (Zea mays) DI KABUPATEN DAIRI - Berton Sianturi (Jurnal Pertanian Tropik, 2017)
Crassocephalum crepidioides on Cornfields in Dairi Regency had been reported tobecome more difficult to control using paraquat. The objective of the research was todetermine the characteristics and the distribution of C.crepidioides resistant to paraquatin cornfields. The experiment was carried out in two steps, the first step was screeningthe population of C. crepidioides with paraquat at the recommended dose, and the secondstep, dose-response experiment for the resistance level of C. crepidioides population withdose 0, 76, 152, 304,5, 609, 1218, and 2436 g.ai /ha. In the first step experiment, paraquatdichloride was applied at 280 g.ai/ha. The treatments were arranged in a randomized blockdesign with 3 replication. The second step experiment was that the resistant populationsconfirmed in the first experiment were sprayed for their dose-response. The treatmentswere arranged in a randomized complete block design (CRBD). The results showed thatof 30 populations of C. crepidiodes, 19 populations (63.3%) were categorized to beresistant with the mortality ranging from 10.84% to 52.08%, and 11 populations (36.7%),was categorized as high resistance with mortality of 0% to 9.21%. The level ofresistance (R/S) of R-C25, R-C27, and R-C30 populations of C. crepidioides were 12,3,14,86, and 24,83 times consecutively, compared with the susceptible population. Thenumber of C. crepidioides chlorophyl leaves in susceptible populations was significantlylower than that of a resistant populations.